Consecuencias normativas de la naturaleza - Marambio, Alvarado (Sapientia, 2006)
The concept of Natural Law requires characteristically the idea that there is a Human Nature with precise normative consequences. This work explores in what sense one should say that a nature (in general) can have such normative consequences. First, two frequent and traditional objections are exposed and summarily dismissed. Second, the structure of a nature with normative consequences is discussed in some detail. It will be contended that such a nature requires an evaluative independent element that cannot be simply "deduced" or otherwise inferred from the other elements that appear there. Some epistemological consequences for our knowledge of human nature will be discussed as well as the alíen character that this sort of nature has for the prevailing physicalistic met aphysical view.